Tool bending in New Caledonian crows - Rutz, Christian (R Soc Open Sci, 2016)
‘Betty’ the New Caledonian crow astonished the world when she ‘spontaneously’ bent straight pieces of garden wire into hooked foraging tools. Recent field experiments have revealed that tool bending is part of the species' natural behavioural repertoire, providing important context for interpreting Betty's iconic wire-bending feat. More generally, this discovery provides a compelling illustration of how natural history observations can inform laboratory-based research into the cognitive capacities of non-human animals.